2022
DOI: 10.1186/s12903-022-02465-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the prosthetic index on stress distribution in Morse taper connection implant system and peri-implant bone: a 3D finite element analysis

Abstract: Background The combination of a prosthetic index with Morse taper connection was developed, with the purpose of making prosthetic procedures more precise. However, the presence of the index may compromise the mechanical performance of the abutment. The aim of this study is to evaluate the effect of prosthetic index on stress distribution in implant–abutment-screw system and peri-implant bone by using the 3D finite element methodology. Methods Two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Under vertical and inclined loading, the MT-PS implant system had significantly higher stress levels in the abutment neck and lower stress levels around the peri-implant bone compared to the IH-PM implant system. It concluded that MT-PS with indexing could reduce stresses within cancellous bone, but lead to higher stress concentrations in the abutment neck and greater susceptibility to mechanical complications [ 29 ]. Villarinh's study also supports that indexed tapered abutments may induce greater biomechanical risk in single-crown restorations when under function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under vertical and inclined loading, the MT-PS implant system had significantly higher stress levels in the abutment neck and lower stress levels around the peri-implant bone compared to the IH-PM implant system. It concluded that MT-PS with indexing could reduce stresses within cancellous bone, but lead to higher stress concentrations in the abutment neck and greater susceptibility to mechanical complications [ 29 ]. Villarinh's study also supports that indexed tapered abutments may induce greater biomechanical risk in single-crown restorations when under function.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study evaluated the effects of the prosthetic index on the stress distribution in Morse taper connection implant systems and peri-implant bone. The use of three-dimensional finite element analysis by Zhang et al is a noteworthy advantage because of its ability to accurately display and measure the stress distribution within the implant system and peri-implant bone [ 29 ]. These findings indicated that the Morse taper connection with platform switching (MT-PS) with the index will cause higher stress concentration on the abutment neck than those without index, which is more prone to mechanical complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bite force has no standard value in the medical profession. Previous studies have used occlusal forces ranging from 100 to 500 N [48][49][50]. The bite-force ratio between the vertical and lateral orientations was 5:1 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Since the load applied in this study was the physiological limit of the human body, the maximum stress experienced by the Bespoke 3D-printed titanium alloy plates was lower than the maximum yield stress of titanium alloy [ 19 ], but the maximum stress experienced by the common reconstruction plate exceeded its maximum yield stress. The design of the Bespoke 3D-printed titanium alloy plates may have allowed the stress to be dispersed throughout the material.…”
Section: Discussionmentioning
confidence: 99%